Popular Nationalism Dalam Kebijakan Luar Negeri Tiongkok Terhadap Jepang Pada Sengketa Kepulauan Senkaku/Diaoyu - Trio Sirmareza (Andalas Journal of International Studies (AJIS))
This paper discusses about Popular Nationalism within China’s Foreign Policy towards Japan in the Context of Senkaku/Diaoyu Islands Dispute. Taking Senkaku/Diaoyu Islands’ dispute as the case, it can be conceived that, from two-level game perspective, Chinese government ‘instrumentalizes’ popular nationalism for its foreign policy purposes, i.e. strengthening its international position on the dispute and giving pressure to Japanese government. Practically, while putting pressure to Japan, popular nationalist movement also puts pressure on Chinese government by criticizing the government over its weak foreign policy towards Japan, as well as demanding for Chinese democratization and political change. Chinese government responds this situation by ‘managing’ popular nationalism. The government applies two-sided policy. When popular nationalist movement is favorable for Chinese foreign policy, the government gives popular nationalist a large controlled access to express their anger towards Japan. However, if popular nationalist starts to criticize government, demand for democratization and political change, Chinese government then restricts the movement by using institutional, informational, and ideational resourcesas well as starting to ban any protest and demonstration. This strange policy performed by Chinese government is strategically able to gain domestic support for its foreign policy, and maintain domestic status quo simultaneously.